NSAID HYPERSENSITIVITY AND BASOPHIL ACTIVATION TEST - Viana, Jorge (2015)
Introduction: Allergy to nonsteroidal anti-inflammatory drugs (NSAIDs) is often associated with severe hypersensitivity reactions and with difficult diagnosis. Basophil activation test by flow cytometry with Flow2cast (BAT) is a novel in vitro test for identification of hypersensitivity reactions to these drugs but with some limitations.Clinical case: Young male manifesting chronic urticaria since childhood presented with worsening of hives with angioedema immediately after NSAID intake. Last reaction happened over a year before after lysine acetylsalicylate. Initial BAT for diagnosis with acetylsalicylic acid (ASA) was inconclusive. Drug provocation test (DPT) negative to celecoxib. Another DPT with 700mg of ASA triggered anaphylaxis three hours later with hypoxia and serum tryptase 27.1μg / L. A second BAT had higher basal activation and marked increase with ASA incubation.Discussion: This case shows current BAT recommendation in NSAID hypersensitivity: a negative BAT does not avoid NSAID DPT. However, time between last reaction and BAT seems to influence results.